2014
DOI: 10.1007/s00204-014-1230-x
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity

Abstract: Antagonizing the action of the pregnane X receptor (PXR) may have important clinical implications for preventing inducer-drug interactions and improving therapeutic efficacy. We identified a widely distributed isothiocyanate, allyl isothiocyanate (AITC), which acts as an effective antagonist of the nuclear receptor pregnane X receptor (PXR, NR1I2) and constitutive androstane receptor (CAR, NR1I3). HepG2 cells were used to assay reporter function, mRNA levels, and protein expression. Catalytic activities of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Recent studies showed that treatment of rifampicin causes toxicity and liver injury [20]. Several PXR antagonists, such as ET-743, ketoconazole, FLB-12, sulforaphane, A-792611, polychlorinated biphenyls, coumestrol, aryl sulfonamides and allyl isothiocyanate, have been reported [2129]. CAR antagonists or inverse agonists such as meclizine, clotrimazole and PK11195 have also been discovered [30,31].…”
Section: Pxr and Car In Drug Metabolism And Drug–drug Interactionsmentioning
confidence: 99%
“…Recent studies showed that treatment of rifampicin causes toxicity and liver injury [20]. Several PXR antagonists, such as ET-743, ketoconazole, FLB-12, sulforaphane, A-792611, polychlorinated biphenyls, coumestrol, aryl sulfonamides and allyl isothiocyanate, have been reported [2129]. CAR antagonists or inverse agonists such as meclizine, clotrimazole and PK11195 have also been discovered [30,31].…”
Section: Pxr and Car In Drug Metabolism And Drug–drug Interactionsmentioning
confidence: 99%
“…In these reports, the main focus was the inhibition of PXR, and that of CAR was studied only for comparison purposes. These reported compounds include the quinoline alkaloid camptothecin [38], the antihyperglycemic agent metformin [39], the natural compound allyl isothiocyanate [40], and the antifungal ketoconazole [41]. We note that most known inhibitors of hCAR are also PXR activators, confounding the use of these molecules in instances of both receptors being present and functional.…”
Section: Car Inhibitorsmentioning
confidence: 99%
“…The enzymes that convert PCM to NAPQI are controlled by hepatic nuclear receptors such as the constitutive androstane receptor (CAR) and the pregnane X receptor (PXR). In vitro studies have demonstrated that blocking CAR/PXR activity renders hepatocytes more resilient to otherwise toxic PCM levels . Risks of this approach are the concurrent shutdown glutathione synthesis from NAC.…”
Section: Managing Paracetamol Overdosementioning
confidence: 99%